O PODER JUDICIÁRIO E A RESPONSABILIDADE INTERNACIONAL: Uma interface entre a denegação de justiça ao estrangeiro e a sujeição do Estado brasileiro à jurisdição supranacional. - MADEIRA, João Bruno Farias (2018)
The international responsibility of the State is pointed out, in the 21st century, as one of the most pressing issues in international law, in reason of the act of making it the epistemological center of the institutions of any justice system. As part of the state structure, the Judiciary has the duty to safeguard international commitments and ensure rights to the human person, it be national or foreigner. In this context, the general research problem is to investigate the legal feasibility of an effective international accountability of the Brazilian State, in the civil sphere, in function of the imputation of illicit to an organ or agent of the Judiciary that contradicts in the work practice norm of jus gentiumin detriment of the foreigner. It is argued, therefore, with support in the dialectic methodology of implication-complementarity, that the violation of international treaties by the patriot courts has the power to generate the responsibility of Brazil if the elements of attribution and illicit fact are configured. It is defended that the non-use of the criteria of national treatment and of the international minimum to the foreign person is conduct liable to international responsibility. It is analyzed, based on normative and sociological precepts, the singularity of the treatment given to foreigners in Brazil and the international commands which grant it essential rights, it’s assessing whether decisions handed down by Brazilian courts in which the non-national is a party may be considered as deniers of rights. The cases in which Brazilian State effectively denies justice to foreigners and the international means of accountability, with imputation of responsibility, are enumerated with support in a quantitative-qualitative study. It addresses the legal consequences of international responsibility for the Brazil, in order to reach the conclusion that the hypotheses of denial of justice to foreigners are modalities of prohibition of recurrent foreigner rights in the practice of the national courts and that the duties of fulfillment of the obligation, the cessation of wrongdoing and redress are indispensable to the maintenance of security in international relations.